ENSURING THE QUALITY OF HIGH EDUCATION BY MEANS OF INSTITUTIONAL AUDIT: THEORETICAL ASPECTS - Forkutsa О. Оlena (Theory and Practice of Public Administration, 2020)
The given article regards the theoretical approaches to ensuring the quality of high education by means of institutional audit. The essence of institutional audit is described in the educational sphere and interpreted within the regulatory-legal framework of Ukraine. It has been determined that institutional audit should be considered as a procedure for external evaluation of the activity of processes, which take place at the educational institution in accordance with its functions of educational nature for their execution and control, thus providing sustainable development and effective functioning of this institution on the basis of innovation, transparency, culture and partnership with other educational institutions. The procedure of conducting an institutional audit is analyzed for secondary educational institutions. It has been noted that institutional audit is intended to replace the former attestation of schools, which audited and controlled their activity. As argued, institutional audit is a fundamentally new procedure, being a method of assessing the quality of educational activity at secondary educational institutions, since until now schools had to undergo attestation in terms of control and verification of their activity, which was too formalized and ineffective. It is substantiated that institutional audit aims at increasing public trust in educational process, taking place at secondary educational institutions, as well as improving the quality of educational services rendered therein. The main trends of institutional audit at secondary educational institutions are also considered. The experience of the developed countries in evaluating the educational process at schools has been analyzed. The necessity of introducing positive experience of the developed countries is substantiated with respect to applying institutional audit within Ukrainian realia. It has been shown that institutional audit in Ukraine will not harm the educational process, on the contrary – it will help secondary educational institutions to develop in order to improve the quality of their educational services. As proved, assurance of the quality of high education by means of institutional audit will let improve functioning of educational institutions by reducing the level of bureaucracy and by increasing the level of transparency of their activity. This, in its turn, it will help to improve the educational services rendered for population at secondary educational institutions in Ukraine.